DESIGN AND FABRICATION OF A WIND SIMULATOR FOR RENEWABLE ENERGY TRAINING AND RESEARCH IN NIGERIA - Daniel, Aliu; Balogun, Vincent Aizeobeoje; Momoh, Muyideen Omuya (FUDMA Journal of Sciences, 2025)
Every year, the laboratory offers a variety of teachings, demonstrations, and initiatives related to renewable energy. Different researchers match the needs of the students' work depending on the area of activity. However, little is achieved in Nigerian institutions regarding wind energy research and demonstration. The lack of laboratory facilities for the training of students in wind turbine technology could be one of the reasons. The proposed Framework is a scaled-down version of the available wind turbine power plant. The proposed device would make it possible to work with students at Nigeria Universities, to practice the wind turbine simulator in a working and configurable model. The simulator gives insight into the various components and implications of changes to the operating points of any wind turbine in light of the wind speed and the pitch angle. Students will learn concepts such as the I-V characteristics of a wind energy system, cut-off, cut-in velocity, and power output. It would also enable the user to control the wind speed externally. The proposed wind lab will also be worthwhile for conducting a wind resource evaluation at various sites. Wind resource assessment, like other technical projects, needs planning and coordination. The developed wind simulator lab is beneficial in real-time data monitoring to justify further site-specific investigations, to compare areas to identify relative developmental potential, to get representative data to estimate the performance and/or economic viability of selected wind turbines, and to monitor the potential for wind turbine use because of it cost-effectiveness.
Keywords: Wind Lab; Training; Wind Energy; Wind Turbine Model; Simulator